2011
DOI: 10.1149/2.007112jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Native Oxide Surface Layer on the Electrochemical Performance of Si Nanoparticle-Based Electrodes

Abstract: This study controllably reduces the silicon dioxide (SiO 2 ) layer on Si nanoparticles and evaluates its effect on the performance of Si nanoparticle-based electrodes in Li-ion batteries. Various thicknesses of this native oxide are present on Si nanoparticles generated by chemical vapor deposition (CVD) due to the process conditions and exposure to oxygen during storage. This layer can be effectively reduced by hydrofluoric acid (HF) etching, which results in improved electrochemical performance over as-recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
115
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 25 publications
2
115
0
Order By: Relevance
“…In fact, a lower lithiation capacity due to an incomplete surface reaction has been observed in recent experiments [15,52,53].…”
Section: Stress Effect On the Lithiation Reactionmentioning
confidence: 83%
“…In fact, a lower lithiation capacity due to an incomplete surface reaction has been observed in recent experiments [15,52,53].…”
Section: Stress Effect On the Lithiation Reactionmentioning
confidence: 83%
“…40 The reason for the rather small electron transfer rate constant was the native SiO 2 surface layer of the Si electrode ( Figure 1b) which causes high impedance also evident from electrochemical impedance spectroscopy (EIS). 41 The ME current i T was locally increased at the edge of the upper left pillar in Figure 2a at x = 20 μm/y = 220 μm (circle symbol), because i T amounted to 2.8 nA and was even 0.5 nA larger than i T,∞ ≈ 2.3 nA. Therefore, it can be concluded that the local electron transfer rate constant at this position was much larger than at all other positions of the Si pillars.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we should concern more about increased and accelerated native oxide surface derived from nanosized silicon materials with large surface area, which can affect the electrochemical performance and induce the inevitable use of hydrofluoric acid (HF). [43,44] The first-cycle Coulombic efficiency of silicon anode is typically in the range of 65-85%, far below that of commercial graphite anodes (90-94%). Below we will summarize the recent progress to achieve high initial Coulombic efficiency from three aspects, including secondary structure design, prelithiation, and electrolyte additive.…”
mentioning
confidence: 99%